Peran UPTD PPA dalam Pemenuhan Hak Asasi Korban Kekerasan terhadap Perempuan dan Anak di Kota Bandung - Nabila Fitria Almadea (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Gender-based and age-based violence targeting women and children continues to pose a serious challenge to human rights protection in Indonesia. As the principal duty bearer, the state bears the obligation to respect, protect, and fulfill victims' rights through effective protection mechanisms, one of which is the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA). This research analyzes the contribution of UPTD PPA Bandung City in fulfilling the human rights of victims of violence against women and children and maps the obstacles encountered in operational service delivery. The study utilizes a juridical-empirical method with a descriptive-analytical approach. Primary data were gathered through in-depth interviews with UPTD PPA Bandung City representatives in November 2025, whereas secondary data were derived from the examination of legal regulations and relevant scholarly literature. Research findings reveal that UPTD PPA Bandung City managed 382 cases in 2025 by providing complaint mechanisms, assessment procedures, legal and psychological support, counseling services, and shelter facilities. These services demonstrate normative compliance with national legislation and human rights principles, particularly concerning protection, rehabilitation, and access to justice. Nevertheless, service delivery encounters several challenges, including insufficient human resources and facilities, underreporting by victims, and suboptimal cross-institutional coordination. Consequently, strengthening institutional capacity, ensuring adequate infrastructure, developing integrated standard operating procedures, and establishing regional regulatory frameworks are essential to guarantee effective and sustained fulfillment of victims' rights.